Exercise referral to promote cardiovascular health in stroke and TIA patients: a pilot feasibility study. Issue 1 (31st October 2020) - Baig, Sheharyar; Moyle, Bethany; Redgrave, Jessica; Majid, Arshad; Ali, Ali
Abstract : Objectives: Exercise programmes studied after stroke often involve specialist supervision. Determine the feasibility and safety for people with stroke (PwS) or transient ischaemic attack (TIA) participating in readily accessible, non-stroke specialised, community-based exercise programmes. Methods: Participants were recruited into a structured, group-based, 12-week programme of aerobic and resistance exercise delivered two times per week at one of five local leisure centres. Completion rates, successful attainment of intended exercise intensity (Borg Rating of Perceived Exertion (RPE)) and safety outcomes were recorded. Measures of physical activity (International Physical Activity Questionnaire), health-related quality of life (EQ-5D) and blood pressure (BP) were recorded at baseline and day 1 post intervention. Results: 79% of participants completed >75% of the intended sessions, with >90% attainment of intended RPE. Exercise was safe with no serious and very few minor adverse events related to exercise. Exercise led to significant increases in EQ-5D (Best of Health p<0.001), levels of weekly moderate physical activity (p<0.001) and decreases in systolic BP (mean change [95% CI]=−5.4 mmHg [−2.84 to −7.96]; p<0.001). Conclusion: Generalised exercise programmes delivered through existing local services, appears feasible, safe and may improve quality of life, physical activity and systolic BP, for PwS and TIA.